Correlação entre lisina e proteína no milho opaco-2 - Sérgio Saraiva, Luiz; Anderson, John C; de Almeida Filho, José (Revista Ceres, 2025)
The relationship of level of protein and lysine, respective- ly, was determined in the endosperm and germ separately for the seeds of the opaque-2 variety Maya 50.